2017
DOI: 10.1016/j.adolescence.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Negative reactions to monitoring: Do they undermine the ability of monitoring to protect adolescents?

Abstract: This study focused on adolescents' negative reactions to parental monitoring to determine whether parents should avoid excessive monitoring because adolescents find monitoring behaviors to be over-controlling and privacy invasive. Adolescents (n = 242,Mage = 15.4 years; 51% female) reported monitoring, negative reactions, warmth, antisocial behavior, depressive symptoms, and disclosure. Adolescents additionally reported antisocial behavior, depressive symptoms, and disclosure one to two years later. In cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 72 publications
0
20
0
1
Order By: Relevance
“…Overall, these results suggest that when parents solicit for information, adolescents may perceive and interpret this practice either as a sign of caring or as an intrusion in their private life (Bakken & Brown, 2010;Laird et al, 2018). Previous research suggests that this may, in part, depend upon adolescents' beliefs about the legitimacy of parental authority, namely "the extent to which parents' assertion of control over an area is believed to be a natural or an appropriate extension of their role as parents" (Darling, Cumsille, & Martinez, 2008, p. 1103.…”
mentioning
confidence: 86%
“…Overall, these results suggest that when parents solicit for information, adolescents may perceive and interpret this practice either as a sign of caring or as an intrusion in their private life (Bakken & Brown, 2010;Laird et al, 2018). Previous research suggests that this may, in part, depend upon adolescents' beliefs about the legitimacy of parental authority, namely "the extent to which parents' assertion of control over an area is believed to be a natural or an appropriate extension of their role as parents" (Darling, Cumsille, & Martinez, 2008, p. 1103.…”
mentioning
confidence: 86%
“…The first includes feeling frustrated, controlled, or invaded by the parents' behavior. This construct has been labeled negative emotional reactions in previous work (LaFleur, Zhao, Zeringue, & Laird, ; Laird, Zeringue, & Lambert, ), and is similar to need frustration as operationalized by Van Petegem, Soenens, Vansteenkiste, and Beyers (). Adolescents experience high levels of behavioral and psychological control as over‐controlling (Kakihara & Tilton‐Weaver, ), and the adolescent likely feels frustrated, controlled, and/or invaded by the parents’ behavior and these emotional reactions may be expressed through internalizing or externalizing symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…However, adolescents may view some forms of parental monitoring as snooping or invasion of privacy (e.g., Hawk et al 2008). Although there are several forms of monitoring (see Laird et al (2018) for an excellent discussion), in the current paper, monitoring generally refers to parents' behaviors (e.g., asking questions about child behaviors).…”
Section: Parental Monitoringmentioning
confidence: 96%
“…Few studies focus on the effects of parental monitoring with respect to cyberbullying (Elsaesser et al 2017). Although some studies caution that adolescents may have a negative reaction to parental monitoring (Hessel et al 2017;Laird et al 2018), emerging studies suggest a negative relationship between parental monitoring and cyberbullying victimization/perpetration (Chang et al 2015;Hemphill and Heerde 2014;Hong et al 2016;Khurana et al 2015). Hong et al (2016) found that parental monitoring-measured by parental knowledge of youth's friends, free time, and activities-was negatively related to both face-to-face bullying and cyberbullying.…”
Section: Parental Monitoringmentioning
confidence: 99%